Islamic Theological Controversy on Theodicy and Destiny: A Clash of Islamicity and Indonesianity - Nurkhalis, Nurkhalis (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2024)
The discourse of Islamic theology among Muslim scholars has experienced fierce debates related to takfiri (in the Ali group) and mihnah (Mu'tazilah scholars' investigation of Qadi) on human deeds, including the persecution of followers of the Wahdatul Wujud school in Indonesia. This article aims to examine theodity in the debate to avoid killing and disbelieving behavior and interpret the destination in the conflict between oral and literal theological firqah that affects active evil due to evil inspired by the ability to achieve shallow believers (ijmali), simple believers (tafshili), complete believers (tafshilimutammim), perfect believers (tafshili mukammil) and special believers (tafshili khususiyat). This article is a literal study that examines the theoretical thinking of Islamic firqah with critical analysis. This article finds that oral theology always adheres to the essence leading to sophisticated logic, while literal theology holds to the truth of the combined interpretation of reason-revelation. Oral theology is a theology without reference to the book of mu'tabarah (legacy) so that theological discussions are often framed in freespeech while literal theology obliges itself to hold on to the book of mu'tabarah. The logic of theology rests on the logic of burhani and kammiyah which is patterned of tanzih-tasbih (pure-holy) and nafi-itsbat (negation-inaugurate).